Responsible and ethical use of artificial intelligence in language education: a systematic review - Zainuddin, Nurkhamimi; Suhaimi, Nur Azlin; Jaffar, Mohammad Najib; Md Norwawi, Norita; Sahrir, Muhammad Sabri; Wan Daud, Wan Ab Aziz; Abdul Ghani, Mohammad Taufiq (Bilingual Publishing Group, 2024)
A plethora of publications have shed light, particularly on the affordances of artificial intelligence (AI) in language education, garnering significant attention, promising transformative impacts on teaching and learning practices. However, the rapid adoption of AI tools has raised ethical concerns regarding data privacy, bias and academic integrity. in response to these concerns, this systematic review aims to explore the responsible and ethical use ofAI in language education (REALE) by examining recent literature from 2020 to 2024. The structure of this research revolves around two key questions: What are the emerging patterns and practices in REALE? and What research methodologies have been utilized in studies examining REALE? The researchers selected 9 studies from 65 publications in the Web of Science (WoS) and Scopus databases, following a rigorous screening process based on predefined inclusion and exclusion criteria. These selected studies were analyzed using thematic codes: the objective of the study, methodologies applied, sample, country and the key outcomes reported. The findings reveal a growing trend towards implementing AI in language education, with an emphasis on ethical training and awareness. The review suggests the necessity for educators and policymakers to develop comprehensive guidelines for the responsible and ethical use of AI in language education. It also recommends further research into inclusive and ethical AI practices across different educational levels to foster a more equitable and responsible use of technology in language education.